First record of the invasive dwarf surf clam Mulinia lateralis (Say 1822) in the eastern Pacific Ocean - Britzke, Ricardo (2022)
Mulinia lateralis is a native bivalve from the Western Atlantic Ocean, distributed from the Gulf of Saint Lawrence in Canada to Yucatan in Mexico. Based on morphological and genetic data of specimens collected in shrimp farms, in this work, we confirm the presence of M. lateralis in the Gulf of Guayaquil, Ecuador. Presence and its consequences of this invasive bivalve in the region is discussed.